2023
DOI: 10.4314/ahs.v23i1.24
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality and survival probability distribution among patients on tuberculosis treatment in Vihiga County, Kenya

Abstract: Background: Tuberculosis (TB) related mortality remains a serious impediment in ending TB epidemic. Objective: To estimate survival probability and identify predictors, causes and conditions contributing to mortality among TB patients in Vihiga County. Methods: A cohort of 291 patients from 20 purposively selected health facilities were prospectively considered. Data was obtained by validated questionnaires through face-to-face interviews. Survival probabilities were estimated using Kaplan-Meier me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Among these patients, 672 (2.68%) tested positive for HIV and had TB/HIV coinfection, while the rest of the patients had negative HIV test results. Meanwhile, other studies investigating TB/HIV coinfection have reported different rates of infection, such as a study in Nigeria that reported a 22.50% coinfection rate among TB patients over 5 years [ 30 ], or a study in Kenya, conducted by Wekunda et al that reported a 35.00% coinfection rate [ 31 ]. Another study conducted on HIV/AIDS patients over 18 years of age in Turkey found that 5.30% of these patients had active tuberculosis at the same time [ 32 ], while a study in China, done by Wang et al that examined only EPTB patients reported a 7.00% coinfection rate [ 33 ], compared to 2.00% in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Among these patients, 672 (2.68%) tested positive for HIV and had TB/HIV coinfection, while the rest of the patients had negative HIV test results. Meanwhile, other studies investigating TB/HIV coinfection have reported different rates of infection, such as a study in Nigeria that reported a 22.50% coinfection rate among TB patients over 5 years [ 30 ], or a study in Kenya, conducted by Wekunda et al that reported a 35.00% coinfection rate [ 31 ]. Another study conducted on HIV/AIDS patients over 18 years of age in Turkey found that 5.30% of these patients had active tuberculosis at the same time [ 32 ], while a study in China, done by Wang et al that examined only EPTB patients reported a 7.00% coinfection rate [ 33 ], compared to 2.00% in the present study.…”
Section: Discussionmentioning
confidence: 99%